2010
DOI: 10.1159/000315152
|View full text |Cite
|
Sign up to set email alerts
|

The Multifactorial Nature of Retinal Vascular Disease

Abstract: Retinal vascular disease is the most common cause of macular edema (ME). While there are several etiologies of vascular compromise and subsequent macular leakage, diabetic retinopathy is the most prevalent and continues to challenge ophthalmologists and frustrate patients due to its refractory nature. In response to this epidemic, diabetic ME (DME) along with cystoid ME (CME) have been areas of active investigation both in the clinic and the laboratory. Several decades of basic science research have revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 104 publications
0
13
0
Order By: Relevance
“…Macular oedema can occur at any stage of the disease and therefore may not always be driven by the same cytokines that drive retinopathy severity. This important disparity and the various morphological subtypes of macular oedema as defined by optical coherence tomography (OCT) have led researchers to lend importance to other insults such as inflammatory pathways . Several pro‐inflammatory pathways are being explored in diabetic retinopathy and diabetic macular oedema, but there are likely to be multiple inciting factors for inflammation.…”
Section: Pathogenesismentioning
confidence: 99%
“…Macular oedema can occur at any stage of the disease and therefore may not always be driven by the same cytokines that drive retinopathy severity. This important disparity and the various morphological subtypes of macular oedema as defined by optical coherence tomography (OCT) have led researchers to lend importance to other insults such as inflammatory pathways . Several pro‐inflammatory pathways are being explored in diabetic retinopathy and diabetic macular oedema, but there are likely to be multiple inciting factors for inflammation.…”
Section: Pathogenesismentioning
confidence: 99%
“…Research into the pathophysiology of ME has led to a greater understanding of the underlying mechanisms and the role of inflammatory mediators that facilitate cellular damage, leading to accumulation of fluid within the retina. 1 , 2 The anti-inflammatory, antiangiogenic, and antipermeability effects of corticosteroids counteract three key pathologic processes involved in the development of ME. 2 , 3 However, the efficacy of corticosteroids is greatly affected by the route of administration.…”
Section: Introductionmentioning
confidence: 99%
“…126 It was further suggested that corticosteroids may inhibit PLA2 and downstream products, for example, prostaglandins and leukotrienes, as well as inhibit adhesion signalling pathway components, including ICAM-1, IL-6, VEGF-A, and stromal cell-derived factor-1, which are involved in vascular permeability and leucocytosis (inflammation). 127 Steroids may also inhibit TJ disassembly. Further elucidation of the cellular mechanisms underlying increased permeability in diabetes and hyperglycaemia, and the effects of different pharmacologic agents and their interactions is required.…”
Section: Scientific Basismentioning
confidence: 99%